Effects of Fish Skin Gelatin Hydrolysates Treated with Alcalase and Savinase on Frozen Dough and Bread Quality - Tekle, Sefik; Ozulku, Gorkem; Bekiroglu, Hatice; Sagdic, Osman (MDPI, 2024)
Fish skin gelatin, as a waste product of sea bream, was used to obtain fish gelatin hydrolysate (FGH) with the treatment of alcalase (alc) and savinase (sav). The functional properties of FGHs and their usage possibilities in frozen dough bread making were investigated. FGH treated with alc showed a higher emulsifying stability index (189 min), while FGH treated with sav showed greater foaming capacity (27.8%) and fat-binding capacity (1.84 mL/g). Bread doughs were produced using two FGHs (alc and sav) and their combination (FGH-alc + FGH-sav). Using FGH treated with these enzymes individually was more effective than their combination in terms of polyacrylamide gel electrophoresis (SDS-PAGE) results and bread quality (specific volume and hardness). The addition of FGH into bread dough showed no significant effect on bread dough viscoelasticity (tan delta), while the increment level of tan delta value for control dough was higher than the dough containing FGH after frozen storage (-30 C-degrees for 30 days). The highest freezable water content (FW%) was found in control dough (33.9%) (p < 0.05). The highest specific volume was obtained for control fresh bread and bread with FGH-alc, while the lowest volume was obtained for fresh bread containing FGH-sav (p < 0.05). After frozen storage of the doughs, the bread with FGH-alc showed the highest specific volume. FGH addition caused a significant reduction in the L* (lightness) value of fresh bread samples when compared to control bread (p < 0.05). This study suggested that usage of FGH-alc in bread making decreased the deterioration effect of frozen storage in terms of the specific volume and hardness of bread.
Keywords: sea bream gelatin; enzymatic hydrolysis; frozen storage of bread dough; bread quality; WHEAT GLUTEN PROTEINS; FUNCTIONAL-PROPERTIES; ANTIOXIDANT PEPTIDES; STORAGE; YEAST; WATER; Food Science & Technology